Implementasi Motion Graphic Tata Cara Umroh Pada Pt. Rhean Citra Oetama - Adelia Khairunnisa; Maidel Fani (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2021)
Making a Motion Graphic on the procedure for implementing this Umrah is a form of information media that is made to keep up with technological developments. The design of this motion graphic is intended to help prospective Umrah pilgrims with less reading interest. By delivering interesting and interactive media, it is hoped that it can increase interest in learning, and make it easier to understand the correct Umrah procedures. The design of this application uses the Luther-Sutopo method with several stages, namely, concept, design, material collecting, assembly, testing and distribution. In motion graphics, there are typography, back sound, dubbing and instruments. The result of this research is Motion Graphic Umrah procedure at PT. Rhean Citra Oetama presented in MP4 format. The results of the analysis of alpha testing and beta testing by getting an average percentage value of 86% and 89%, where the percentage value falls into the category of response scale strongly agrees. Based on the alpha and beta tests that have been carried out, the motion graphic video at PT Rhean Citra Oetama as a learning medium can convey information on Umrah procedures and prospective Umrah pilgrims understand and understand Umrah procedures. Make it easier for prospective Umrah pilgrims to understand and learn and memorize prayers before carrying out the Umrah worship.